Knowing your custmers. - ROWLEY, Jennifer (1997)
Explores the concept of customer for library and information services, and notes the role of users, influences and deciders. Advises that in order to offer an effective service to customers, it is important to identify the benefits sought by different groups or segments, and to understand the customer decision-making process which is important in determining 'purchase' behaviour and the use of the service.